MUSINGS ON THE EVANGELIZING MISSION OF THE CHURCH IN A PLURALISTIC WORLD: RAHNER, VATICAN II, AND THE ROLE OF THE LAITY - Jeanmarie Gribaudo, (Asian Horizons, 2015)
In this short article, the author looks at the post-Vatican II evangelizing mission of the Church in light of its transition to a global Church. The need for dialogue and openness to the Spirit are raised as the Church continues to develop ways to speak of its mission to “go out to all the world and tell the Good News” and to enter into dialogue with other religions. The indispensable role of the laity is also considered, though not in depth. Rahner’s contribution to this discussion though basically limited to volume 20 of Theological Investigations is significant. Rahner’s understanding of modern humanity and his ability to address the necessity of holding questions of ambiguity in tension give a way forward for evangelization and dialogue with other religions for the 21st century.